Repetition, Feedback, and Temporality in Two Compositions by William Basinski - Jackson, David (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
In this essay I examine how William Basinski’s loop-based recordings reveal and extend the aesthetic concurrence between technological, biological, and human duration, memory, and the perception of the industrial temporal object. The examination of how looping stresses a composition’s flow in the perception of a time-based media object and the exchange between memory and the machine as a performance and configuration of the mental sphere, pursues a line of thought that brings together ideas about repetition in Basinski’s compositions as a sonic reformatting of the mental sphere and the technology of Basinski’s slow, analog, compositions contra the accelerated digitalism of twenty-first-century life.